STRATEGI MANAJERIAL KEPALA SEKOLAH DALAM MENGOPTIMALKAN SUMBER BELAJAR DAN LINGKUNGAN SOSIAL UNTUK MENINGKATKAN KINERJA SEKOLAH DASAR DI KECAMATAN KASEMEN - Sopian Sopian; Ahmad Mukhlis; Andriani Andriani (STAI Darul Qalam Tangerang, 2025)
Elementary school performance is the main indicator of the effectiveness of educational institutions in achieving academic goals and strengthening the character of students. However, the difference in performance achievement between schools with relatively equal facilities shows that managerial factors and the social environment have a significant contribution to the quality of the institution. This study aims to analyze the managerial strategy of school principals in optimizing learning resources and social environment to improve the performance of elementary schools in Kasemen District. This study uses a qualitative approach with multiple case study designs in